Hollow particles and uses thereof

CN117651604BActive Publication Date: 2026-10-27MATSUMOTO YUSHI SEIYAKU CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280046518.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-05
Filing Date
2022-03-28
Publication Date
2026-10-27
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

[0003]通常,由于中空粒子轻量,因此发生飞散等,操作性低

Benefits of technology

[0024]本发明的中空粒子轻量,且操作性和分散性优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117651604B_ABST
    Figure CN117651604B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a light-weight hollow particle excellent in operability and dispersibility and use thereof. A hollow particle comprising a shell portion containing a thermoplastic resin and a hollow portion surrounded by the shell portion, the true specific gravity d1 of the hollow particle being 0.02 to 0.1, satisfying the following Condition 1. The ash content is preferably 2.5% by weight or less. Condition 1: the true specific gravity d1 and the loose specific gravity d2 of the hollow particle have the following formula (I). 58 ≤ 100 × (d1 - d2) / d1 ≤ 78 Formula (I).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hollow particles and their uses. Background Technology

[0002] Thermally expandable microspheres with a thermoplastic resin shell and a foaming agent encapsulated inside are generally called thermally expandable microcapsules. Furthermore, by heating and expanding these microcapsules, hollow particles with a hollow interior can be obtained. These hollow particles are lightweight and are used and researched in a wide range of fields, including adhesives, lightweight coatings, and thermal insulation coatings.

[0003] Hollow particles are typically lightweight and prone to scattering, resulting in poor operability. To improve their operability, methods such as attaching inorganic powders to their surface have been employed. However, attaching inorganic powders increases the specific gravity of the hollow particles, which can compromise their inherent lightweight properties.

[0004] In addition, Patent Document 1 illustrates a thermally foamable microsphere, characterized in that the residual rate of the foamed particles formed by free foaming at a temperature higher than the foaming start temperature, as determined by a blower test on the glass plate, is more than 3% by mass relative to the total mass of the foamed particles before the blower test. The illustration shows that the adhesion between the formed foamed particles and between the foamed particles and other materials is excellent, the loss of foamed particles is minimal, and the mechanical properties of the resulting molded article are good.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2016 / 088800 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] However, in the hollow particles obtained by heating the thermally foamed microspheres of Patent Document 1, the hollow particles fuse with each other and with other materials. In addition, in the manufacturing equipment using the hollow particles, there is severe adhesion to the equipment, which confirms that the operability of the hollow particles is reduced and the dispersibility is also reduced.

[0010] The object of this invention is to provide lightweight hollow particles with excellent operability and dispersibility, and their uses, in response to the problems described above.

[0011] Methods for solving problems

[0012] The inventors conducted in-depth research and found that hollow particles with specific properties can solve the above-mentioned problems, thus completing the present invention.

[0013] That is, the present invention provides hollow particles each comprising a shell portion containing a thermoplastic resin and a hollow portion enclosed by the shell portion, wherein the true specific gravity d1 of the hollow particles is 0.02 to 0.1, and the hollow particles satisfy the following Condition 1.

[0014] Condition 1: The true specific gravity d1 and the loose bulk specific gravity d2 of the hollow particles satisfy the relationship represented by the following formula (I).

[0015] 58≤100×(d1-d2) / d1≤78 Formula (I)

[0016] The ash content of the hollow particles of the present invention is preferably 2.5% by weight or less.

[0017] The average particle diameter of the hollow particles of the present invention is preferably 1 to 100 μm.

[0018] The thermoplastic resin in the hollow particles of the present invention is preferably a polymer of a polymerizable component containing a nitrile-based monomer.

[0019] The hollow particles of the invention preferably satisfy the following Condition 2.

[0020] Condition 2: The pH at 25°C of an aqueous dispersion obtained by dispersing the hollow particles in ion-exchanged water is higher than 7, and the content of the hollow particles in the aqueous dispersion is 1% by weight.

[0021] The composition of the present invention is a composition comprising the above hollow particles and a base material component.

[0022] The molded article of the present invention is a material obtained by molding the above composition.

[0023] Effects of the Invention

[0024] The hollow particles of the present invention are lightweight, and are excellent in handleability and dispersibility.

[0025] Since the composition of the present invention contains the above hollow particles, it has no uneven distribution, and is uniformly, stably lightweight.

[0026] Since the molded body of the present invention is a material obtained by molding the above composition, it is lightweight. Brief Description of the Drawings

[0027] Figure 1 is a schematic diagram showing an example of the hollow particles.

[0028] Figure 2 is a schematic diagram of a foaming process section of a production apparatus for producing hollow particles by a dry heating expansion method. Detailed Description of the Embodiments

[0029] The hollow particles of the present invention are formed of an outer shell containing thermoplastic resin and a hollow portion surrounded by the outer shell. Hereinafter, the hollow particles of the present invention will be described in detail.

[0030] [Hollow particles]

[0031] The hollow particles of the present invention comprise an outer shell containing thermoplastic resin and a hollow portion surrounded by the outer shell, for example, as shown in the figure. Figure 1 As shown. Hollow particles are (approximately) spherical, with a hollow section inside that is equivalent to a large cavity. If we use an everyday object to illustrate its shape, we can give an example of a soft tennis ball.

[0032] The hollow particles of the present invention can also be expanded bodies of thermally expandable microspheres, as described later.

[0033] The hollow particle's outer shell is surrounded by its outer and inner surfaces, has no ends, and has a continuous shape. While uniformity is preferred for the thickness of the outer shell, i.e., the distance between the outer and inner surfaces, non-uniformity is also permissible.

[0034] The hollow part of a hollow particle is basically filled with gas, but it can also be a liquid substance. A single large hollow part is generally preferred, however, multiple hollow parts can exist within a hollow particle.

[0035] The true specific gravity d1 of the hollow particles of the present invention is 0.02 to 0.1. If the true specific gravity d1 is within the above range, it becomes lightweight. However, if the true specific gravity d1 is less than 0.02, the scattering tendency increases, and the operability decreases. The upper limit of the true specific gravity d1 is preferably 0.095, more preferably 0.09, and particularly preferably 0.085. On the other hand, the lower limit of the true specific gravity d1 is preferably 0.025, more preferably 0.028, and particularly preferably 0.030.

[0036] It should be noted that the true specific gravity d1 of the hollow particles is a value obtained using the method described in the embodiments of the present invention.

[0037] The hollow particles of this invention satisfy the following condition 1.

[0038] By ensuring that the hollow particles satisfy the aforementioned true specific gravity d1 and the following condition 1, the hollow particles will not become a state of firm aggregation and / or adhesion caused by fusion, or a state of separation due to extremely high fluidity. Instead, they will become a state of aggregated mass that can be separated by a weak external force. Therefore, not only can the dispersion of hollow particles be suppressed, but also the firm fusion and / or adhesion of hollow particles can be suppressed. The hollow particles have excellent operability and dispersibility.

[0039] Condition 1: The true specific gravity d1 and the loose specific gravity d2 of the hollow particles have the following relationship (I).

[0040] 58≤100×(d1-d2) / d1≤78 Equation (I)

[0041] If the value of formula (I) above is less than 58, the hollow particles become lightweight and highly fluid separated particles, thus easily scattering and reducing operability. On the other hand, if the value of formula (I) above is greater than 78, the hollow particles become particles in a state of firm aggregation and / or adhesion caused by fusion, thus increasing adhesion to equipment, reducing operability, and reducing dispersibility. The upper limit of the value of formula (I) above is preferably 77, more preferably 76, further preferably 75, particularly preferably 73, and most preferably 71. On the other hand, the lower limit of the value of formula (I) above is preferably 60, more preferably 61, further preferably 63, particularly preferably, and most preferably 65.

[0042] The loose density d2 of the hollow particles in this invention is not particularly limited, but is preferably 0.0045 to 0.05. If the loose density d2 is 0.0045 or higher, the dispersibility of the hollow particles tends to improve. On the other hand, if the loose density d2 is 0.05 or lower, the operability of the hollow particles tends to improve. The upper limit of the loose density d2 is more preferably 0.04, and even more preferably 0.035. On the other hand, the lower limit of the loose density d2 is more preferably 0.0055, even more preferably 0.007, and particularly preferably 0.0085.

[0043] It should be noted that the loose specific gravity d2 of the hollow particles is a value obtained using the method described in the embodiments of the present invention.

[0044] The ash content of the hollow particles in this invention is not particularly limited, but is preferably 2.5% by weight or less. If the amount of ash is within the above range, it becomes a collection of hollow particles that can be separated by a weak external force, and tends to exert the effects of this invention more effectively. The upper limit of the amount of ash is preferably in the following order: (1) 2.3% by weight, (2) 2% by weight, (3) 1.7% by weight, (4) 1.5% by weight, (5) 1% by weight, (6) 0.8% by weight, and (7) 0.5% by weight (the larger the value in parentheses, the more preferred). On the other hand, the lower limit of the amount of ash is preferably 0% by weight, more preferably 0.1% by weight, and even more preferably 0.2% by weight.

[0045] It should be noted that the ash content of the hollow particles in this invention refers to the strongly heated residue of the hollow particles, which is a value obtained using the method described in the embodiments of this invention.

[0046] The hollow particles of the present invention are not particularly limited, however, it is preferred that they satisfy the following condition 2.

[0047] Condition 2: The pH of the aqueous dispersion obtained by dispersing the hollow particles in ion-exchanged water is greater than 7 at 25°C, and the content of the hollow particles in the aqueous dispersion is 1% by weight.

[0048] If the pH of the aqueous dispersion in condition 2 above at 25°C is greater than 7, it tends to be easily controlled into a state resembling an aggregate of hollow particles with a degree of separability. The upper limit of this pH is preferably 14, more preferably 12, further preferably 10.5, and particularly preferably 10. On the other hand, the lower limit of this pH is more preferably 7.2, further preferably 7.5, particularly preferably 8, and most preferably 8.5.

[0049] It should be noted that the pH at 25°C is a value obtained using the method described in the embodiments of the present invention.

[0050] The average particle size of the hollow particles in this invention is not particularly limited, but is preferably 1 to 100 μm. If the average particle size is within the above range, there is a tendency to improve the operability and dispersibility of the hollow particles, such as their scattering and adhesion properties. The upper limit of this average particle size is more preferably 80 μm, further preferably 60 μm, and particularly preferably 50 μm. On the other hand, the lower limit of this average particle size is more preferably 10 μm, further preferably 15 μm, particularly preferably 20 μm, and most preferably 22 μm.

[0051] It should be noted that the average particle size of the hollow particles is a value obtained using the method described in the embodiments of the present invention.

[0052] The variation coefficient CV of the particle size distribution of the hollow particles in this invention is not particularly limited, but it is preferably 50% or less, more preferably 45% or less, further preferably 40%, and particularly preferably 35% or less. When the variation coefficient is greater than 50%, since hollow particles with different particle sizes come into contact in the gaps between particles, the result is a tendency for the number of contact points between particles of different sizes to increase, and there is a situation where hollow particles are firmly aggregated and / or bonded together. The lower limit of this variation coefficient CV is preferably 3%, more preferably 5%, and particularly preferably 10%. This variation coefficient CV is calculated using the following calculation formulas (1) and (2).

[0053] [Mathematical Expression 1]

[0054] CV=(s / <x>)×100(%)···(1)

[0055]

[0056] (In the formula, s is the standard deviation of particle size) <x>x is the average particle size. i Let n be the particle size of the i-th particle and n be the number of particles.

[0057] The ratio (r1 / r2) of the average particle size of the hollow particles in this invention to the thickness of the outer shell (r1) is not particularly limited, but it is preferably 0.001 to 0.01 from the viewpoint of effective lightweight.

[0058] The outer shell of the hollow particle of the present invention is formed of a thermoplastic resin. The thermoplastic resin is not particularly limited, but preferably is a polymer with polymeric components, namely, a polymer containing a monomeric component as a monomer having one polymeric carbon-carbon double bond, and may also contain a polymeric component containing a crosslinking agent as a monomer having at least two polymeric carbon-carbon double bonds.

[0059] Monomer components contained in polymerizable substances include, for example, nitrile monomers such as acrylonitrile, methacrylonitrile, fumaric acid, and maleic acid; halogenated vinylidene monomers such as vinyl chloride; dihalogenated vinylidene monomers such as vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl butyrate; unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethylacrylic acid, crotonic acid, and cinnamic acid; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, citraconic acid, and chloromaleic acid; anhydrides of unsaturated dicarboxylic acids; monomethyl maleate, monoethyl maleate, monobutyl maleate, monomethyl fumarate, monoethyl fumarate, monomethyl itaconic acid, monoethyl itaconic acid, monobutyl itaconic acid, and other unsaturated dicarboxylic acid monoesters containing carboxyl groups; methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-(meth)acrylate. (Methacrylic acid) ester monomers include ethylhexyl ester, stearyl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; (meth)acrylamide monomers include acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; maleimide monomers include N-phenylmaleimide and N-cyclohexylmaleimide; styrene monomers include styrene and α-methylstyrene; olefinic unsaturated monoolefin monomers include ethylene, propylene, and isobutylene; vinyl ether monomers include vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; vinyl ketone monomers include vinyl methyl ketone; N-vinylcarbazole and N-vinylpyrrolidone; vinyl naphthalene salts; and itaconic acid diesters such as dimethyl itaconic acid and dibutyl itaconic acid. Some or all of the carboxyl groups in monomers containing carboxyl groups can be neutralized during or after polymerization.

[0060] Sometimes acrylic acid or methacrylic acid are referred to together as (meth)acrylic acid, (meth)acrylic acid class refers to acrylic acid or methacrylic acid, and (meth)acrylic ester refers to acrylate or methacrylate.

[0061] These monomeric components can be used alone or in combination of two or more.

[0062] If the polymerizable component includes nitrile monomers as monomer components, it is preferable from the perspective of improving the heat resistance and gas barrier properties of the outer shell of the hollow particles. The weight percentage of the nitrile monomers in the polymerizable component is not particularly limited, but is preferably 15 to 100% by weight. The upper limit of this weight percentage is more preferably 99.9% by weight, further preferably 99.5% by weight, particularly preferably 99% by weight, and most preferably 98.5% by weight. On the other hand, the lower limit of this weight percentage is more preferably 20% by weight, further preferably 30% by weight, particularly preferably 40% by weight, and most preferably 50% by weight.

[0063] When the polymerizable component contains a nitrile monomer, from the perspective of improving the mechanical strength of the outer shell, it is preferable that the nitrile monomer contains acrylonitrile and / or methacrylonitrile, and it is even more preferable that acrylonitrile must be included.

[0064] When the nitrile monomer includes acrylonitrile, the weight percentage of acrylonitrile in the polymerizable component is not particularly limited, but is preferably 40 to 100% by weight. The upper limit of this weight percentage is more preferably 95% by weight, further preferably 90% by weight, particularly preferably 85% by weight, and most preferably 80% by weight. On the other hand, the lower limit of this weight percentage is more preferably 50% by weight, further preferably 55% by weight, and particularly preferably 60% by weight.

[0065] From the perspective of improving the density of the outer shell, it is preferable that the nitrile monomers include acrylonitrile (AN) and methacrylonitrile (MAN).

[0066] When the nitrile monomers include AN and MAN, the weight ratio of AN to MAN (AN / MAN) is not particularly limited, but is preferably 40 / 60 to 99 / 1. The upper limit of this weight ratio is more preferably 90 / 10, further preferably 87 / 13, and particularly preferably 80 / 20. On the other hand, the lower limit of this weight ratio is more preferably 50 / 50, further preferably 55 / 45, and particularly preferably 60 / 40.

[0067] If the polymerizable component contains a monomer with a carboxyl group as a monomer component, it is preferred from the perspective of improving the heat resistance and solvent resistance of the outer shell.

[0068] When the polymerizable component contains a monomer containing a carboxyl group, the weight percentage of the carboxyl-containing monomer in the polymerizable component is not particularly limited, but is preferably 10 to 80% by weight. The upper limit of this weight percentage is more preferably 70% by weight, further preferably 60% by weight, particularly preferably 50% by weight, and most preferably 45% by weight. On the other hand, the lower limit of this weight percentage is more preferably 15% by weight, and further preferably 20% by weight.

[0069] If the polymerizable component includes (meth)acrylate as a monomer, the glass transition temperature of the outer shell can be adjusted, which is preferable from the perspective of being able to adjust the manufacturing conditions of the hollow particles. The weight percentage of (meth)acrylate in the polymerizable component is not particularly limited, but is preferably 0 to 70% by weight. The upper limit of this weight percentage is more preferably 60% by weight, further preferably 50% by weight, particularly preferably 35%, and most preferably 20%. On the other hand, the lower limit of this weight percentage is more preferably 0.2% by weight, further preferably 0.5% by weight, particularly preferably 0.7% by weight, and most preferably 1% by weight.

[0070] If the polymerizable component includes a vinylidene monomer as a monomer component, it is preferable from the perspective of improving the gas barrier properties of the thermoplastic resin. The weight percentage of the vinylidene monomer in the polymerizable component is not particularly limited, but is preferably 0 to 70% by weight. The upper limit of this weight percentage is more preferably 60% by weight, further preferably 50% by weight, particularly preferably 35%, and most preferably 20%. On the other hand, the lower limit of this weight percentage is more preferably 0.2% by weight, further preferably 0.5% by weight, particularly preferably 0.7% by weight, and most preferably 1% by weight.

[0071] As mentioned above, the polymerizable component may contain a crosslinking agent. If the polymerizable component contains a crosslinking agent, the resulting thermoplastic resin has improved density, which is preferable from the perspectives of improved expansion, heat resistance, and mechanical strength.

[0072] Examples of crosslinking agents include aromatic divinyl compounds such as divinylbenzene; allyl methacrylate, triacryloyl methyl acetal, triallyl isocyanate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, poly(1,4-butanediol diacrylate), 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di... Multifunctional (meth)acrylate compounds, such as PEG#200 di(meth)acrylate, PEG#400 di(meth)acrylate, PEG#600 di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, and tricyclodecanediethanol di(meth)acrylate, can be used. One or more of these crosslinking agents can be used.

[0073] The polymerizable component may not contain a crosslinking agent; however, if the polymerizable component does contain a crosslinking agent, its amount is not particularly limited, but is preferably 0.01 to 10 parts by weight relative to 100 parts by weight of the monomer component. The upper limit of this content is more preferably 0.1 parts by weight, further preferably 0.3 parts by weight, and particularly preferably 0.5 parts by weight. On the other hand, the lower limit of this content is more preferably 6 parts by weight, further preferably 3.5 parts by weight, particularly preferably 1.6 parts by weight, and most preferably 1.1 parts by weight.

[0074] [Methods for manufacturing hollow particles]

[0075] For the hollow particles of the present invention, a manufacturing method including step 1 (expansion step) can be cited, in which thermally expandable microspheres containing a shell of thermoplastic resin and an inner foaming agent that vaporizes upon heating are heated and expanded. Furthermore, prior to the expansion step, thermally expandable microspheres need to be manufactured. A manufacturing method including step 2 (polymerization step) can be cited, in which the polymerizing components are polymerized using a polymerization initiator in an aqueous dispersion medium containing an oily mixture containing the aforementioned polymerizable components and foaming agent. Therefore, the hollow particles can be manufactured by sequentially performing a polymerization step and an expansion step.

[0076] For the hollow particles of the present invention, from the viewpoint of efficiently obtaining hollow particles, it is preferable to manufacture them by means of a process of heating and expanding thermally expandable microspheres as shown in the above expansion process.

[0077] (Polymerization process)

[0078] The foaming agent can be any substance that vaporizes upon heating as described above. Examples include hydrocarbons with 3 to 13 carbon atoms, such as propane, iso)butane, iso)pentane, iso)hexane, iso)heptane, iso)octane, iso)nonane, iso)decane, iso)undecane, iso)dodecane, and iso)tridecane; hydrocarbons with more than 13 carbon atoms but less than 20 carbon atoms, such as iso)hexadecane and iso)eicosane; and substances with a primary boiling point of 150–260 °C and / or a distillation range of 70 °C. Hydrocarbons such as n-alkanes and isoalkanes, petroleum fractions, etc., at temperatures up to ~360℃; halogenated hydrocarbons with 1 to 12 carbon atoms, such as chloromethane, dichloromethane, chloroform, and carbon tetrachloride; fluorinated compounds such as hydrofluoroethers; silanes with 1 to 5 carbon atoms, such as tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, and trimethyl-n-propylsilane; and compounds that generate gas through thermal decomposition upon heating, such as azodicarbonamide, N,N'-dinitrospentamethylenetetramine, and 4,4'-oxobis(benzenesulfonylhydrazine). The blowing agent can consist of one compound or a mixture of two or more compounds. The blowing agent can be linear, branched, or alicyclic, preferably aliphatic.

[0079] In the polymerization process, by polymerizing the above-mentioned polymerizable components, a thermoplastic resin that forms the shell of thermally expandable microspheres can be produced.

[0080] Furthermore, in the polymerization process, it is preferable to polymerize the polymerizable component in the presence of a polymerization initiator. The polymerization initiator may be included in the oily mixture along with the polymerizable component and the foaming agent.

[0081] There are no particular limitations on the polymerization initiator; examples include peroxides such as dicarbonates, peroxide esters, and acyl peroxides; and azo compounds such as azo nitrile, azo esters, azo amides, azo alkyls, and polymeric azo initiators. These polymerization initiators can be used individually or in combination of two or more. It should be noted that oil-soluble polymerization initiators that are soluble in the polymerizable component are preferred.

[0082] There is no particular limitation on the amount of polymerization initiator, however, it is preferably 0.05 to 10 parts by weight relative to 100 parts by weight of the polymerizable component, more preferably 0.1 to 8 parts by weight, and even more preferably 0.2 to 5 parts by weight.

[0083] During the polymerization process, the oily mixture may further contain chain transfer agents, etc.

[0084] Aqueous dispersion media are media with water as the main component, such as ion-exchanged water, used to disperse oily mixtures. They may further contain hydrophilic organic solvents such as methanol, ethanol, propanol, and acetone. In this invention, "hydrophilic" means that the medium is miscible with water. There is no particular limitation on the amount of aqueous dispersion media used; however, 100 to 1000 parts by weight of aqueous dispersion media are preferred relative to 100 parts by weight of the polymerizable component.

[0085] The aqueous dispersion medium may further contain an electrolyte. Examples of electrolytes include sodium chloride, magnesium chloride, calcium chloride, sodium sulfate, magnesium sulfate, ammonium sulfate, and sodium carbonate. One or more of these electrolytes may be used alone or in combination. There is no particular limitation on the content of the electrolyte; however, it is preferable to contain 0.1 to 50 parts by weight relative to 100 parts by weight of the aqueous dispersion medium.

[0086] The aqueous dispersion medium may contain at least one water-soluble compound selected from potassium dichromate, alkali metal salts of nitrite, metal (III) halides, boric acid, water-soluble ascorbic acid derivatives, water-soluble polyphenols, water-soluble B vitamins, and water-soluble phosphonic acids (salts); polyalkylene imines having a structure in which an alkyl group substituted with a hydrophilic functional group selected from carboxylic acid (salt) groups is bonded to a nitrogen atom; and water-soluble 1,1-substituted compounds having a structure in which a hydrophilic functional group selected from hydroxyl, carboxylic acid (salt) groups is bonded to a heteroatom on the same carbon atom. It should be noted that, in this invention, "water-soluble" means a state in which more than 1 g dissolves in 100 g of water.

[0087] There is no particular limitation on the amount of water-soluble compounds contained in the aqueous dispersion medium; however, it is preferably 0.0001 to 1.0 parts by weight, more preferably 0.0003 to 0.1 parts by weight, and even more preferably 0.001 to 0.05 parts by weight, relative to 100 parts by weight of the polymerizable component.

[0088] Aqueous dispersion media may contain dispersants and stabilizing agents in addition to electrolytes and water-soluble compounds.

[0089] There are no particular limitations on the types of dispersion stabilizers used; examples include calcium phosphate, magnesium pyrophosphate obtained by metathesis, calcium pyrophosphate, colloidal silica, alumina sol, and magnesium hydroxide. These dispersion stabilizers can be used individually or in combination of two or more.

[0090] Regarding the amount of dispersant stabilizer, it is preferably 0.05 to 100 parts by weight relative to 100 parts by weight of polymerizable component, and more preferably 0.2 to 70 parts by weight.

[0091] There are no particular limitations on what constitutes a dispersion stabilizing agent; examples include polymeric dispersion stabilizing agents, cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants. These dispersion stabilizing agents can be used individually or in combination of two or more.

[0092] Aqueous dispersion media can be prepared, for example, by adding electrolytes, water-soluble compounds, dispersing stabilizers, and dispersing stabilizing aids to water (ion-exchanged water) as needed. The pH of the aqueous dispersion media during polymerization can be appropriately determined based on the types of water-soluble compounds, dispersing stabilizers, and dispersing stabilizing aids.

[0093] In the polymerization process, polymerization can be carried out in the presence of sodium hydroxide, or sodium hydroxide and zinc chloride.

[0094] In the polymerization process, an oily mixture is suspended and dispersed in an aqueous dispersion medium in a manner that prepares spherical oil droplets of a given particle size.

[0095] Methods for suspending and dispersing oily mixtures include, for example, stirring using a homogenizer (e.g., Primix), static dispersion devices such as static mixers (e.g., Noritake Engineering Co., Ltd.), membrane suspension, and ultrasonic dispersion.

[0096] Then, suspension polymerization is initiated by heating the dispersion in which the oily mixture is dispersed in the form of spherical oil droplets in an aqueous dispersion medium. In the polymerization reaction, it is preferable to stir the dispersion, for example, only slowly enough to prevent the monomers from floating and the thermally expandable microspheres from settling after polymerization.

[0097] The polymerization temperature can be freely set according to the type of polymerization initiator, but it is preferably controlled within the range of 30 to 100°C, more preferably within the range of 40 to 90°C. The reaction temperature is preferably maintained for about 1 to 20 hours. There is no particular limitation on the initial polymerization pressure, but it is within the range of 0 to 5 MPa, more preferably 0.2 to 3 MPa, measured by gauge pressure.

[0098] The obtained slurry is filtered using a centrifuge, a pressure press, a vacuum dewatering machine, etc., to produce a cake with a moisture content of 10-50% by weight, preferably 15-45% by weight, and more preferably 20-40% by weight. The cake is then dried using a tray dryer, an indirect heating dryer, a flow dryer, a vacuum dryer, a vibration dryer, an airflow dryer, etc., to produce a dried powder with a moisture content of 5% by weight or less, preferably 3% by weight or less, and more preferably 1% by weight or less.

[0099] Alternatively, the slurry can be dried using a spray dryer, a flow dryer, or similar equipment to obtain dried powder.

[0100] By operating as described above, thermally expandable microspheres are obtained comprising a shell containing a thermoplastic resin and an inner foaming agent that vaporizes upon heating.

[0101] The average particle size of the thermally expandable microspheres obtained by the polymerization process is not particularly limited, but it is preferably 1 to 75 μm, more preferably 2 to 50 μm, even more preferably 3 to 40 μm, particularly preferably 5 to 35 μm, and most preferably 7 to 30 μm.

[0102] The true specific gravity of the thermally expandable microspheres obtained by the polymerization process is preferably 0.97 to 1.30, more preferably 1.05 to 1.20. If the true specific gravity of the thermally expandable microspheres is within the above range, there is a tendency to efficiently obtain the hollow particles of the present invention.

[0103] (Expansion process)

[0104] The expansion process is not particularly limited as long as it involves heating and expanding the thermally expandable microspheres obtained from the polymerization process; it can be either a dry heating expansion method or a wet heating expansion method.

[0105] As a dry heating expansion method, the method described in Japanese Patent Application Publication No. 2006-213930 can be cited, and in particular, the internal injection method can be cited. As a wet heating expansion method, the method described in Japanese Patent Application Publication No. 62-201231, etc. The preferred temperature for heating and expanding the thermally expandable microspheres is 80 to 450°C.

[0106] In the case where the hollow particles of the present invention are expanded bodies of thermally expandable microspheres, the hollow particles may possess expansion margin. The so-called expansion margin of hollow particles refers to the property that the hollow particles will further expand (re-expansion) if heated.

[0107] The expansion allowance ratio of the hollow particles is not particularly limited, but is preferably 18% to 85%. If the expansion allowance ratio is less than 18%, the frequency of contact between the hollow particles during the expansion process increases, and the heat load tends to increase. As a result, the hollow particles become particles that have undergone strong agglomeration and / or adhesion due to fusion, etc., increasing their adhesion to equipment, etc., leading to reduced operability and reduced dispersibility. On the other hand, if the expansion allowance ratio is greater than 85%, it is impossible to obtain lightweight hollow particles, thus failing to achieve the lightweight effect. The upper limit of the expansion allowance ratio is more preferably 80%, further preferably 70%, particularly preferably 65%, and most preferably 60%. On the other hand, the lower limit of the expansion allowance ratio is more preferably 25%, further preferably 30%, particularly preferably 35%, and most preferably 40%.

[0108] It should be noted that the expansion margin of thermally expandable microspheres is usually above 95%.

[0109] The expansion margin of hollow particles represents the degree of expansion of the hollow particles relative to the maximum re-expansion. The true specific gravity (d1) and the true specific gravity (d) of the hollow particles at maximum re-expansion are measured. A ), which can be calculated using the following formula (3).

[0110] Expansion margin (%) = (1-d) A / d1)×100 (3)

[0111] It should be noted that when hollow particles have expansion capacity, their maximum re-expansion state is when hollow particles are obtained from thermally expandable microspheres, the hollow particles contain a component that can be vaporized by heating to expand the thermally expandable microspheres, namely a foaming agent, and the hollow particles can maintain the limit state of the foaming agent.

[0112] Furthermore, when the hollow particles of the present invention are expanded bodies of thermally expandable microspheres, the hollow particles may contain a foaming agent. The content of the foaming agent in the hollow particles is not particularly limited, but is preferably 0.5 to 25% by weight. The upper limit of this content is more preferably 20% by weight, further preferably 15% by weight, particularly preferably 12% by weight, and most preferably 10% by weight. On the other hand, the lower limit of this content is more preferably 1% by weight, further preferably 2% by weight, and particularly preferably 3% by weight. It should be noted that the content of the foaming agent in the hollow particles refers to the weight ratio of the foaming agent relative to the hollow particles.

[0113] The product containing hollow particles and thermally expandable microspheres obtained by the above method has components other than the aforementioned electrolytes, water-soluble compounds, dispersing stabilizers, and dispersing stabilizing aids. These components can be adjusted to a given amount, or they can be removed.

[0114] When the product is a dispersion containing hollow particles and thermally expandable microspheres, it can be obtained, for example, by dispersing the hollow particles and thermally expandable microspheres in a liquid dispersion medium such as water. Alternatively, a slurry containing thermally expandable microspheres after the polymerization process or a slurry containing hollow particles after the expansion process can also be used as a dispersion.

[0115] Since the electrolytes, water-soluble compounds, and dispersing stabilizers are water-soluble, their quantities can be adjusted by washing the hollow particles, thermally expandable microspheres, and the aforementioned thermally expandable microspheres in a wet cake with water.

[0116] Since the dispersant stabilizer is a poorly soluble inorganic compound, its amount can be adjusted through a process called pH adjustment. This involves adjusting the pH to convert the poorly soluble inorganic compound into a water-soluble inorganic compound via an acid-base reaction (pH adjustment reaction), thus removing it from the surface of the hollow particles and thermally expandable microspheres. After the pH adjustment process, the dispersion medium is filtered, and the resulting hollow particles and thermally expandable microspheres are washed with water to adjust the amount of the poorly soluble inorganic compound.

[0117] For example, when the dispersant is a sparingly soluble alkaline inorganic compound such as magnesium hydroxide or calcium carbonate, acidic substances such as sulfuric acid or hydrochloric acid can be used to adjust the pH of the aqueous dispersion medium containing the thermally expandable microspheres to 2.0–5.0, thereby transforming it into a water-soluble inorganic compound such as magnesium sulfate, magnesium chloride, or calcium chloride, thus performing a pH adjustment process. On the other hand, when the dispersion medium is a sparingly soluble acidic inorganic compound such as colloidal silica, alkaline substances such as sodium hydroxide or potassium hydroxide can be used to adjust the pH to preferably 9.5 or higher, more preferably 10 or higher, further preferably 10.5 or higher, and particularly preferably 11 or higher, thereby transforming it from a gelled state under colloidal silica into a silicate dissolved in water, thus performing a pH adjustment process.

[0118] In the pH adjustment process, heating can be performed to promote the water solubility of sparingly soluble inorganic compounds based on acid-base reactions. Through this pH adjustment process, the dispersant stabilizer adhering to the surface of the thermally expandable microspheres becomes a water-soluble inorganic compound, which is then removed along with electrolytes, water-soluble compounds, and dispersant stabilizers by washing with water. This allows for the adjustment of the ash content of the hollow particles and the thermally expandable microspheres.

[0119] The pH adjustment step can be performed after the polymerization step or after the expansion step. From the viewpoint of efficiently manufacturing the hollow particles of the present invention, it is preferable to perform the pH adjustment step after the polymerization step.

[0120] [Compositions and molded articles]

[0121] The composition of the present invention comprises the hollow particles and substrate components described above.

[0122] Examples of base material components include rubbers such as natural rubber, butyl rubber, silicone rubber, and ethylene-propylene-diene rubber (EPDM); thermosetting resins such as unsaturated polyester, epoxy resin, and phenolic resin; waxes such as polyethylene wax and paraffin wax; ethylene-vinyl acetate copolymer (EVA), ionomers, polyethylene, polypropylene, polyvinyl chloride (PVC), acrylic resins, thermoplastic polyurethane, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polystyrene (PS), polyamide resins (nylon 6, nylon 66, etc.), polycarbonate, and polyethylene terephthalate. The substrates include thermoplastic resins such as polyethylene glycol ester (PET), polybutylene terephthalate (PBT), polyacetal (POM), and polyphenylene sulfide (PPS); thermoplastic elastomers such as olefin-based elastomers and styrene-based elastomers; bioplastics such as polylactic acid (PLA), cellulose acetate, PBS, PHA, and starch resins; sealing materials such as silicone-based, modified silicone-based, polysulfide-based, modified polysulfide-based, urethane-based, acrylic-based, polyisobutylene-based, and butyl rubber-based materials; coating components such as urethane-based, ethylene-vinyl acetate copolymer-based, vinyl chloride-based, and acrylic-based materials; and inorganic materials such as cement, mortar, and cordierite. These substrate components can be used individually or in combination of two or more.

[0123] In addition to the hollow particles and the substrate components, the compositions of the present invention may also contain other components that are appropriately used according to the application.

[0124] The composition of the present invention can be prepared by mixing the above-described substrate component with hollow particles. Alternatively, the substrate component can be mixed with hollow particles to obtain a mixture, and the resulting mixture can be further mixed with the substrate component to prepare the composition of the present invention.

[0125] The hollow particles of the present invention are lightweight and have excellent operability and dispersibility, thus enabling the production of uniform and stable lightweight compositions without unevenness.

[0126] In the compositions of the present invention, the content of hollow particles is not particularly limited; however, it is preferably 0.1 to 20 parts by weight relative to 100 parts by weight of the base material. If the content is within the above range, a lightweight composition that maintains the physical properties of the base material can be obtained. The upper limit of this content is more preferably 15 parts by weight, further preferably 13 parts by weight, and particularly preferably 10 parts by weight. On the other hand, the lower limit of this content is more preferably 0.3 parts by weight, further preferably 0.5 parts by weight, and particularly preferably 1.0 parts by weight.

[0127] Methods for mixing hollow particles with substrate components include, for example, using kneaders, rollers, mixing rollers, mixers, single-shaft mixers, twin-shaft mixers, multi-shaft mixers, etc.

[0128] Examples of uses for the compositions of the present invention include molding compositions, coating compositions, clay compositions, fiber compositions, adhesive compositions, powder compositions, etc.

[0129] The molded article of the present invention can be obtained by molding the above-described composition. Examples of molded articles, coatings, and other molded articles of the present invention can be cited as examples.

[0130] The molded articles of the present invention can improve various physical properties such as lightweight, porosity, sound absorption, heat insulation, low thermal conductivity, low dielectric constant, designability, impact absorption, and strength.

[0131] Example

[0132] The following describes specific embodiments of the hollow particles of the present invention. It should be noted that the present invention is not limited to these embodiments. In the following embodiments and comparative examples, unless otherwise specified, "%" means "weight %" and "parts" means "parts by weight".

[0133] For the thermally expandable microspheres and hollow particles mentioned in the following manufacturing examples, embodiments, and comparative examples, their physical properties are measured according to the procedures shown below, and their performance is evaluated.

[0134] [Determination of the average particle size and particle size distribution of thermally expandable microspheres]

[0135] The Microtrac particle size analyzer (model 9320-HRA) from Nikkiso Corporation was used as the measuring device, and the D50 value measured based on volume was set as the average particle size.

[0136] [Determination of the average particle size and particle size distribution of hollow particles]

[0137] A laser diffraction particle size distribution analyzer (Mastersizer 3000) manufactured by Malvern was used as the measuring device, and the dry method was employed for determination. The average particle size was set as the D50 value based on a volumetric reference.

[0138] [Expansion start temperature of thermally expandable microspheres (T)] s ) and maximum expansion temperature (T max [Determination of]

[0139] A DMA (DMAQ800 model, manufactured by TA Instruments) was used as the measuring apparatus. 0.5 mg of microspheres was added to an aluminum cup with a diameter of 6.0 mm and a depth of 4.8 mm. An aluminum cap (5.6 mm in diameter and 0.1 mm thick) was placed on top of the microsphere layer to prepare the sample. The sample height was measured with a 0.01 N force applied from above using a pressure device. The sample was heated from 20 °C to 300 °C at a heating rate of 10 °C / min with a 0.01 N force applied using the pressure device, and the vertical displacement of the pressure device was measured. The temperature at which the displacement in the positive direction began was set as the expansion initiation temperature (T). s The temperature at which the maximum displacement is displayed is set as the maximum expansion temperature (T). max ).

[0140] [Determination of Ash Content (Residue from Strong Heating)]

[0141] The dried sample W p (g) Add to a crucible and heat using an electric heater at 700°C for 30 minutes to ashed. The resulting ashed material W q (g) The ash content (C) of the sample was determined by weight. A (by weight) according to W p (g) and W q (g) Calculate using the following formula.

[0142] C A (weight%) = (W q / W p )×100

[0143] Here, thermally expandable microspheres and hollow particles were used as the above-mentioned samples for ash content determination. Furthermore, samples with a moisture content of less than 1% were used in the ash content determination.

[0144] [Determination of moisture content]

[0145] The moisture content of thermally expandable microspheres and hollow particles was determined using a Karl Fischer moisture meter (MKA-510N, manufactured by Kyoto Electronics Industry Co., Ltd.). The moisture content of the thermally expandable microspheres was set as C. w1 .

[0146] [Determination of the foaming agent content in thermally expandable microspheres]

[0147] 1.0 g of thermally expandable microspheres were added to a stainless steel evaporating dish with a diameter of 80 mm and a depth of 15 mm, and their weight (W1(g)) was measured. 30 ml of acetonitrile was added and dispersed evenly, and the weight (W2(g)) after standing at room temperature for 24 hours and then drying under reduced pressure at 130 °C for 2 hours was measured.

[0148] The content of the foaming agent in the thermally expandable microspheres (hereinafter also referred to as the encapsulation rate) is calculated using the following formula (C1).

[0149] C1 (weight %) = 100 × {100 × (W1 - W2) / 1.0 - C} wl } / (100-C w1 )

[0150] (In the formula, the water content C of the thermally expandable microspheres is determined using the above method.) w1 。 )

[0151] [Determination of the true specific gravity d1 of hollow particles]

[0152] The true specific gravity d1 of hollow particles was determined using the following method.

[0153] The true specific gravity was determined using the immersion method (Archimedes method) with isopropanol under an ambient temperature of 25°C and a relative humidity of 50%.

[0154] Specifically, empty a 100cc volumetric flask, dry it, and weigh it (W). B1 (g) Accurately fill the weighed volumetric flask with isopropanol to the meniscus, and weigh the flask filled with 100cc of isopropanol (W). B2 (g)).

[0155] In addition, empty the 100cc volumetric flask, dry it, and weigh it (W). S1 (g) Fill a weighed volumetric flask with approximately 50 cc of hollow granules, adjusting the moisture content to less than 1%, and weigh the volumetric flask containing the hollow granules (W). S2 (g)). Then, isopropanol is accurately added to the meniscus of a volumetric flask filled with hollow particles without introducing air bubbles, and the weight (W) of the flask is measured. S3 (g)). Afterwards, the obtained W B1 W B2 W S1 W S2 and W S3 Import the following formula to calculate the true specific gravity (d1) of the hollow particle. Additionally, the true specific gravity dA of the hollow particle at maximum re-expansion is also calculated using the above method, replacing the hollow particle with one at maximum re-expansion.

[0156] d1={(W S2 -W S1 )×(W B2 -W B1 ) / 100} / {(W B2 -W B1 )-(W S3 -W S2 )}

[0157] [Determination of the specific gravity d2 of hollow particles]

[0158] The specific gravity d2 of hollow particles was determined using the following method.

[0159] Prepare a 100ml cylindrical container (A) made of stainless steel (inner diameter 5.0cm, depth 5.1cm) and weigh it (W3(g)). Then, install an open cylindrical cellcap (B) (mouth diameter 5.2cm, height 5.0cm) on the cylindrical container (A) to prepare the measuring instrument (C).

[0160] Weigh 30g of hollow granules into a polyethylene bag (size 12: 0.03mm × 230mm × 340mm (thickness × width × length)). Secure the bag 100mm from the opening with a rubber band and vibrate it rapidly up and down 10 times with an amplitude of 200mm to allow the hollow granules to flow smoothly. Then, slowly fill the container into the polyethylene bag from a position 30mm above the top of the unit cap (B) of the appliance (C) until it is full. The filling of the appliance (C) with hollow granules is carried out continuously and rapidly after the flowability operation of the hollow granules is performed.

[0161] After filling the container (C) with hollow particles, let it stand for 2 minutes. Then, remove the unit cap (B), scrape off the portion that overflowed from the container (A), and remove the hollow particles while they are still attached to the container (A). Then, weigh the container (A) filled with hollow particles (W4(g)).

[0162] Then, the obtained W3 and W4 are introduced into the following formula to calculate the loose specific gravity d2 of the hollow particles.

[0163] d2=(W4-W3) / 100

[0164] [Determination of pH of an aqueous dispersion containing 1% by weight of hollow particles]

[0165] Add 1g of hollow particles to 99g of ion-exchanged water and mix for 10 minutes at 150rpm using a THREE-ONE MOTOR mixer. Heat and cool as needed to maintain the temperature of the aqueous dispersion at 25°C to prepare the aqueous dispersion.

[0166] The pH of the obtained aqueous dispersion was measured using a pH meter (model: D-71) manufactured by Horiba Manufacturing Co., Ltd.

[0167] <Operability Evaluation of Hollow Particles: Settling Time Evaluation>

[0168] First, as an evaluation of the operability of hollow particles, the significance of using hollow particle settling time evaluation technology will be explained.

[0169] Generally, substances with lower true density settle at a slower rate, while substances with higher true density settle at a faster rate.

[0170] Substances with low true density remain in space for a longer period before falling to the ground, and are more likely to disperse even in slight airflows, thus their operability is considered low. The operability of the hollow particles in this invention is evaluated using their settling time as an indicator.

[0171] In the case of falling matter, it is known that based on the relationship between gravity and air resistance, particle size affects terminal velocity, i.e., settling time. Of course, compared to hollow particles in a separated state, hollow particles forming an aggregate have a larger mass, a faster terminal velocity, and a longer time to reach that velocity. In other words, the settling time of particles is influenced by the state of the hollow particles, and this settling time can be used to evaluate the operability of hollow particles.

[0172] The operability of hollow particles was evaluated using the following methods.

[0173] Prepare a 1L glass graduated cylinder (outer diameter 70mm, height 420mm). Then, weigh the hollow particles according to the weight calculated based on the specific gravity (W5(g), W5=300 / d2) to make it a container with a capacity of 300ml, and fill it into the graduated cylinder.

[0174] The operations described above were then carried out rapidly and continuously.

[0175] Seal the graduated cylinder by capping it, and allow the hollow particles to fall completely (this is considered one cycle). Perform five inverted cycles to allow the hollow particles to flow. Next, once the volume has settled to 300 ml, invert the graduated cylinder again and place it on the settling platform. Measure the time it takes for the volume to settle to 320 ml.

[0176] Based on the measured settlement time (T) d The operability of hollow particles was evaluated using the following indicators.

[0177] ○:T d ≤30s;

[0178] ×:T d >30s.

[0179] <Evaluation of the Dispersion of Hollow Particles>

[0180] In a 350ml container, achieve a volume of 45cm³. 3 The hollow particles were weighed according to the weight calculated based on the true specific gravity d1 (W6(g), W6=45 / d1). 100g of ethylene-vinyl acetate emulsion (SUMIKAFLEX 456HQ) (true specific gravity 1.08g / cm³) was used. 3 Add to the container and mix gently by hand. Then, use a Primix TK HOMO DISPER to stir at 500 rpm for 2 minutes to obtain the complex.

[0181] The obtained composite was coated using a coating machine with a gap of 0.2 mm (5 cm in length × 30 cm in width). The number (N) of aggregates on the surface of the dried coating was measured and evaluated. The dispersibility of hollow particles was evaluated using the following indicators.

[0182] ○: N≤2;

[0183] ×: N>2.

[0184] <Overall Evaluation>

[0185] The following indicators are used to comprehensively evaluate hollow particles.

[0186] ○: Operability is ○, and dispersion is ○.

[0187] ×: Operability is ○, and dispersion is ×.

[0188] ×: Operability is ×, and dispersion is ○.

[0189] ×: Operability is ×, and decentralization is ×.

[0190] <Manufacturing Example A>

[0191] A water-based dispersion medium was prepared by adding 0.9 parts of polyvinylpyrrolidone, 0.1 parts of carboxymethylated polyethylene imine·Na salt, and 38 parts of colloidal silica A dispersion (average particle size 12 nm, effective concentration 20%) to 750 parts of ion-exchanged water and adjusting the pH to 3.

[0192] In addition, 137 parts of acrylonitrile, 91 parts of methacrylonitrile, 12 parts of methyl methacrylate, 1 part of diethylene glycol dimethacrylate, 3 parts of di(2-ethylhexyl) peroxide dicarbonate, 36 parts of isobutane and 9 parts of isopentane are dissolved and mixed to prepare an oily mixture.

[0193] An aqueous dispersion medium was mixed with an oily mixture, and the resulting mixture was dispersed in a homogenizer (Primix, TK HOMOMIXER) at 10,000 rpm for 1 minute to prepare a suspension. This suspension was then transferred to a 1.5 L pressurized reaction vessel and purged with nitrogen to an initial reaction pressure of 0.35 MPa. The mixture was then stirred at 80 rpm and polymerized at 60 °C for 20 hours to obtain polymer solution A.

[0194] <Manufacturing Examples B-E>

[0195] In manufacturing examples B to E, polymer solutions B to E were obtained in the same manner as in manufacturing example A, except that the reaction conditions were changed as shown in Table 1. It should be noted that the colloidal silica B dispersion used in manufacturing example E was a dispersion with an average particle size of 7 nm and an effective concentration of 20%.

[0196] <Example 1>

[0197] The obtained polymerization solution A was dried in a dryer at 40°C for 24 hours to obtain thermally expandable microspheres A. The ash content of the obtained thermally expandable microspheres A was 2.2%. Furthermore, the physical properties of the obtained thermally expandable microspheres A are shown in Table 1.

[0198] Then, the obtained thermally expandable microspheres A were used to manufacture hollow particles using a dry heating expansion method.

[0199] As a dry heating expansion method, the internal injection method described in Japanese Patent Application Publication No. 2006-213930 was adopted. Specifically, the method used is... Figure 2 The manufacturing apparatus shown has a foaming process section, which heats and expands thermally expandable microspheres to produce hollow particles according to the following steps.

[0200] (Explanation from the foaming process department)

[0201] As shown in Figure 3, the foaming process section includes: a gas inlet pipe (not labeled) with a dispersion nozzle (11) at the outlet and disposed in the center; a collision plate (12) disposed downstream of the dispersion nozzle (11); an overheat protection cylinder (10) spaced apart around the gas inlet pipe; and hot air nozzles (8) spaced apart around the overheat protection cylinder (10). In this foaming process section, a gaseous fluid (13) containing thermally expandable microspheres flows in the direction of the arrow inside the gas inlet pipe. In the space formed between the gas inlet pipe and the overheat protection cylinder (10), a gas flow (14) flows in the direction of the arrow to improve the dispersion of the thermally expandable microspheres and prevent overheating of the gas inlet pipe and the collision plate. Furthermore, in the space formed between the overheat protection cylinder (10) and the hot air nozzles (8), a hot air flow for thermal expansion flows in the direction of the arrow. Here, the hot air flow (15) and the gaseous fluid (13) and the gas flow (14) generally flow in the same direction. Inside the overheat protection cylinder (10), a refrigerant flow (9) flows in the direction of the arrow for cooling.

[0202] (Operation of the manufacturing equipment)

[0203] In the spraying process, a gas fluid (13) containing thermally expandable microspheres is flowed into a gas inlet pipe that has a dispersing nozzle (11) at the outlet and is located inside the hot air flow (15), so that the gas fluid (13) is sprayed from the dispersing nozzle (11).

[0204] In the dispersion process, the gaseous fluid (13) is collided with a collision plate (12) located downstream of the dispersion nozzle (11) to disperse the thermally expandable microspheres in the hot air stream (15) without any omissions. Here, the gaseous fluid (13) flowing out of the dispersion nozzle (11) is guided together with the gas stream (14) to the collision plate (12) and collides with it.

[0205] In the expansion process, the dispersed thermally expandable microspheres are heated to above the expansion start temperature in a hot air stream (15) to cause them to expand. Subsequently, the resulting hollow particles are recovered through a cooling section or the like.

[0206] (Expansion conditions and results)

[0207] In Example 1, using Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 1 were obtained by heating a hot air volume of 270℃ at a flow rate of 0.025 / min. The true specific gravity d1 of the obtained hollow particles 1 was 0.025. The loose specific gravity d2 was 0.0084. Other physical properties of hollow particles 1 are shown in Table 2.

[0208] <Example 2>

[0209] In Example 2, using Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 2 were obtained from thermally expandable microspheres A at a hot air temperature of 240℃ and a flow rate of 0.05 / min. The true specific gravity d1 of the obtained hollow particles 2 was 0.05, and the loose specific gravity d2 was 0.02. Other physical properties of hollow particles 2 are shown in Table 2.

[0210] <Example 3>

[0211] The obtained polymer solution A was filtered to obtain a wet cake with a solid content of 62%.

[0212] 450g of the obtained wet cake was added to 1300g of ion-exchanged water, and the mixture was stirred at 200rpm for 3 hours to prepare redispersible liquid A. Redispersible liquid A was filtered and dried at 40℃ for 24 hours to obtain thermally expandable microspheres A-1. The ash content of the obtained thermally expandable microspheres A-1 was 1.7%. Other physical properties of thermally expandable microspheres A-1 were the same as those of thermally expandable microspheres A.

[0213] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 3 were obtained by heating a hot air volume of 200℃ at a flow rate of 0.09 / min. The true specific gravity d1 of the obtained hollow particles 3 was 0.09, and the loose specific gravity d2 was 0.0348. Other physical properties of hollow particles 3 are shown in Table 2.

[0214] <Examples 4 and 5>

[0215] Add 8g of potassium hydroxide aqueous solution (50% concentration) to 1000g of the obtained polymerization solution A, and adjust the pH by stirring at 200 pm for 1 hour at 25°C. The pH of polymerization solution A is 11.2.

[0216] After filtering the pH-adjusted polymerization solution A, 450g of the resulting wet cake (62% solid content) was washed with 450g of deionized water. The washed dispersion was then dried at 40°C for 24 hours to obtain thermally expandable microspheres A-2. The ash content of the obtained thermally expandable microspheres A-2 was 0.2%. Other physical properties of the thermally expandable microspheres A-2 were the same as those of thermally expandable microspheres A.

[0217] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 4 were obtained by heating air at a speed of 100 m / min and a hot air temperature of 265 °C. The true specific gravity d1 of the obtained hollow particles 4 is 0.03, and the loose specific gravity d2 is 0.0074. Other physical properties of hollow particles 4 are shown in Table 2.

[0218] Additionally, using Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 5 were obtained from thermally expandable microspheres A-2 at a hot air temperature of 205℃ and a flow rate of 0.086 / min. The true specific gravity d1 of the obtained hollow particles 5 was 0.086, and the loose specific gravity d2 was 0.025. Other physical properties of hollow particles 5 are shown in Table 2.

[0219] <Examples 6 and 7>

[0220] 8.5 g of potassium hydroxide aqueous solution (50% concentration) was added to 1000 g of polymerization solution B obtained in manufacturing example B, and the pH was adjusted by stirring at 200 pm for 1 hour at 25°C. The pH of polymerization solution B was 11.5.

[0221] After filtering the pH-adjusted polymerization solution B, 450 g of the resulting wet cake (62% solid content) was washed with 450 g of deionized water. The washed dispersion was then dried at 40°C for 24 hours to obtain thermally expandable microspheres B-2. The ash content of the obtained thermally expandable microspheres B-2 was 0.1%. Other physical properties of the thermally expandable microspheres B-2 were the same as those of thermally expandable microspheres B.

[0222] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 6 were obtained by heating a hot air volume of 285℃ at a flow rate of 0.025 / min. The true specific gravity d1 and the loose specific gravity d2 of the obtained hollow particles 6 are 0.0058. Other physical properties of hollow particles 6 are shown in Table 2.

[0223] Additionally, using Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 7 were obtained from thermally expandable microspheres B-2 at a hot air temperature of 265℃ and a flow rate of 0.055 / min. The true specific gravity d1 and the loose specific gravity d2 of the obtained hollow particles 7 are 0.015. Other physical properties of hollow particles 7 are shown in Table 2.

[0224] <Comparative Example 1>

[0225] Hollow particles were manufactured using the dry heating expansion method to produce thermally expandable microspheres A obtained in Example 1.

[0226] use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 8 were obtained by heating a hot air volume of 310℃ at a flow rate of 0.019 / min. The true specific gravity d1 and the loose specific gravity d2 of the obtained hollow particles 8 are 0.0034. Other physical properties of hollow particles 8 are shown in Table 3.

[0227] <Comparative Example 2>

[0228] Hollow particles were manufactured using the dry heating expansion method with thermally expandable microspheres B-2 obtained in Example 6.

[0229] use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 9 were obtained by heating air at a speed of 0.015 m / min and a hot air temperature of 315 °C. The true specific gravity d1 of the obtained hollow particles 9 was 0.015, and the loose specific gravity d2 was 0.001. Other physical properties of hollow particles 9 are shown in Table 3.

[0230] <Comparative Examples 3 and 4>

[0231] The polymerization solution C obtained in manufacturing example C was dried in a dryer at 40°C for 24 hours to obtain thermally expandable microspheres C. The ash content of the obtained thermally expandable microspheres C was 4.2%. Other physical properties of the thermally expandable microspheres C are shown in Table 1.

[0232] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 10 were obtained by heating a hot air volume of 325℃ at a flow rate of 0.011 / min. The true specific gravity d1 of the obtained hollow particles 10 was 0.011, and the loose specific gravity d2 was 0.0021. Other physical properties of hollow particles 10 are shown in Table 3.

[0233] Additionally, using Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 11 were obtained from thermally expandable microspheres C at a hot air temperature of 300℃ and a flow rate of 0.025 / min. The true specific gravity d1 and the loose specific gravity d2 of the obtained hollow particles 11 were 0.012. Other physical properties of hollow particles 11 are shown in Table 3.

[0234] <Comparative Example 5>

[0235] The polymer solution D obtained in manufacturing example D was dried in a dryer at 40°C for 24 hours to obtain thermally expandable microspheres D. The ash content of the obtained thermally expandable microspheres D was 2.2%. Other physical properties of the thermally expandable microspheres D are shown in Table 1.

[0236] 50 parts of thermally expandable microspheres D and 50 parts of calcium carbonate (Whiton SB Red, manufactured by Bikawa Powdered Chemical Industry Co., Ltd.) were added to a separable flask and mixed. The mixture was then heated to 140°C over 5 minutes while stirring to obtain hollow particles 12. The true specific gravity d1 of the obtained hollow particles 12 was 0.044, and the loose specific gravity d2 was 0.0197. Other physical properties of hollow particles 12 are shown in Table 3.

[0237] <Comparative Example 6>

[0238] 7 g of potassium hydroxide aqueous solution (50% concentration) was added to 1000 g of polymerization solution D obtained in manufacturing example D, and the pH was adjusted by stirring at 200 pm for 1 hour at 25°C. The pH of polymerization solution D was 10.6.

[0239] After filtering the pH-adjusted polymerization solution D, 450 g of the resulting wet cake (62% solid content) was washed with 450 g of deionized water. The washed dispersion was then dried at 40°C for 24 hours to obtain thermally expandable microspheres D-2. The ash content of the obtained thermally expandable microspheres D-2 was 0.6%. Other physical properties of the thermally expandable microspheres D-2 were the same as those of thermally expandable microspheres D.

[0240] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 13 were obtained by heating a hot air volume of 330℃ at a flow rate of 0.015 / min. The true specific gravity d1 and the loose specific gravity d2 of the obtained hollow particles 13 were 0.0028. Other physical properties of hollow particles 13 are shown in Table 3.

[0241] <Comparative Example 7>

[0242] The polymerization solution E obtained in manufacturing example E was dried in a dryer at 40°C for 24 hours to obtain thermally expandable microspheres E. The ash content of the obtained thermally expandable microspheres E was 0.5%. Other physical properties of the thermally expandable microspheres E are shown in Table 1.

[0243] Then, use Figure 2 The manufacturing apparatus shown is configured with the following expansion conditions: raw material supply rate of 0.5 kg / min and raw material dispersion gas rate of 0.35 m³ / min. 3 / min, hot air flow rate 8.0m 3 Hollow particles 14 were obtained by heating at a speed of 1 / min and a hot air temperature of 265℃. The true specific gravity d1 of the obtained hollow particles 14 is 0.02, and the loose specific gravity d2 is 0.0011. Other physical properties of hollow particles 13 are shown in Table 3.

[0244] [Table 1]

[0245]

[0246] The details of the abbreviations in Table 1 are shown below.

[0247] AN: Acrylonitrile

[0248] MAN: Methacrylonitrile

[0249] MMA: Methyl methacrylate

[0250] St: Styrene

[0251] IBX: Isoborneol Methacrylate

[0252] TMP: Trimethylolpropane trimethacrylate

[0253] EDMA: Ethylene glycol dimethacrylate

[0254] OPP: di(2-ethylhexyl) peroxide dicarbonate

[0255] AIBN: Azobisisobutyronitrile

[0256] V-65: 2,2'-Azobis(2,4-dimethylpentanonitrile)

[0257] NaCl: Sodium chloride

[0258] PVP: Polyvinylpyrrolidone

[0259] DEA-ADA: A condensate of diethanolamine and adipic acid (effective concentration 50%)

[0260] CMPEI·Na salt: Carboxymethylated polyethyleneimine·Na salt

[0261] AlCl3·6H2O: Aluminum chloride·hexahydrate

[0262] [Table 2]

[0263]

[0264] [Table 3]

[0265]

[0266] <Evaluation>

[0267] The lightweight, manufacturability, and dispersibility of the obtained hollow particles were evaluated using the methods described above. The results are presented in Tables 4 and 5.

[0268] The true specific gravity d1 of the hollow particles in Examples 1 to 7 is 0.02 to 0.1, which satisfies condition 1 above. Therefore, they are lightweight and have excellent operability and dispersibility.

[0269] On the other hand, in Comparative Examples 1-3, 6 and 7, the value of Equation (I) in Condition 1 is greater than 78, and the hollow particles are in a strong condensed and / or bonded state such as fusion, and are not particles with excellent dispersibility.

[0270] In addition, in Comparative Examples 4 and 5, the value of Equation (I) in Condition 1 is less than 58. The hollow particles are not in a state of aggregates that are capable of separation. Therefore, the settling velocity is low, the settling time is long, and the dispersion is high. They are not particles with excellent operability.

[0271] [Table 4]

[0272]

[0273] [Table 5]

[0274]

[0275] Industrial availability

[0276] The hollow particles of this invention can be used as lightweight materials for putty, coatings, inks, sealing materials, mortars, paper clay, ceramics, etc., or after being shaped by injection molding, extrusion molding, pressure molding, etc., they can be used to manufacture foamed molded bodies with excellent sound insulation, heat insulation, heat insulation, sound absorption, etc.

[0277] Explanation of reference numerals in the attached figures

[0278] 1 Outer shell, 2 Hollow section, 8 Hot air nozzle, 9 Refrigerant flow, 10 Overheat protection cylinder, 11 Dispersion nozzle, 12 Collision plate, 13 Gas flow containing thermally expandable microspheres, 14 Gas flow, 15 Hot air flow.< / x> < / x>

Claims

1. A hollow particle comprising an outer shell containing a thermoplastic resin and a hollow portion surrounded by said outer shell. The thermoplastic resin is a polymer containing polymerizable components of nitrile monomers. The polymerizable component comprises a monomer having one polymerizable carbon-carbon double bond and a monomer having at least two polymerizable carbon-carbon double bonds. The monomer having one polymerizable carbon-carbon double bond comprises the nitrile monomer. The nitrile monomer constitutes 30% to 99.5% by weight of the polymerizable component. Relative to 100 parts by weight of the monomer having one polymerizable carbon-carbon double bond, the content of the monomer having at least two polymerizable carbon-carbon double bonds is 0.01 parts by weight to 140 / 240 parts by weight. The true specific gravity d1 of the hollow particles is 0.02 to 0.

1. The hollow particles satisfy the following condition 1: Condition 1: The true specific gravity d1 and the loose specific gravity d2 of the hollow particles have the following relationship (I): 58≤100×(d1-d2) / d1≤78 Equation (I).

2. The hollow particles according to claim 1, wherein the ash content is less than 2.5% by weight.

3. The hollow particles according to claim 1 or 2 have an average particle size of 1 μm to 100 μm.

4. The hollow particle according to claim 1 or 2, wherein, The nitrile monomer includes acrylonitrile, which accounts for 40% to 95% by weight of the polymerizable component.

5. The hollow particle according to claim 1 or 2, wherein it satisfies the following condition 2: Condition 2: The pH of the aqueous dispersion obtained by dispersing the hollow particles in ion-exchanged water is greater than 7 at 25°C, and the content of the hollow particles in the aqueous dispersion is 1% by weight.

6. The hollow particle according to claim 1 or 2, wherein, The hollow particles are expanded bodies of thermally expandable microspheres, and the expansion margin of the hollow particles is 18% to 85%.

7. A composition comprising the hollow particles and substrate components as described in claim 1 or 2.

8. A molded body formed by molding the composition of claim 7.

Citation Information

Patent Citations

  • Preparation of minute foamed body

    JP1987201231A

  • Process for producing thermally expandable microsphere

    JP2006213930A

  • Heat-expanding microspheres having adhesive properties, and method for producing same

    WO2016088800A1

  • Thermal expansion microspheres, manufacturing method and use thereof

    CN106459729A

  • Hollow resin particles and use of same

    CN109476772A